2009
DOI: 10.1007/s11148-010-9234-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of composite deflocculant on the properties of medium-cement heat-resistant concrete

Abstract: Comparative analysis is provided for the properties of medium-cement concrete based on mullite filler in relation to different type of deflocculant. The effect of different deflocculants on concrete structure formation, hydration, rheology, strength and heat resistance is discussed. It is proposed that in concrete with a composite deflocculant it is possible to form nano-structures as a result of which there is a considerable increase in concrete strength after drying at 110°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…6) (Pundene et al 2009). This additive is effective in forming nanostructures during cement hydration.…”
Section: Refractory Concrete Produced Using Microsilica Hybrid Deflocmentioning
confidence: 99%
“…6) (Pundene et al 2009). This additive is effective in forming nanostructures during cement hydration.…”
Section: Refractory Concrete Produced Using Microsilica Hybrid Deflocmentioning
confidence: 99%
“…Previous studies [1] have shown that by means of a composite of two deflocculants (sodium tripolyphosphate and polycarboxylate ester Castament FS-20) it is possible to control the rate of hydration and formation of the structure of medium-cement heat-resistant concrete during hardening. It was established that it was possible to increase concrete strength properties considerably: after firing at 1200ºC the ultimate strength in compression of concrete with a composite deflocculant (160 MPa) exceeds by almost a factor of two the strength of concrete in which only one of the deflocculants is used (80 -100 MPa).…”
Section: Introductionmentioning
confidence: 99%